IDDF2020-ABS-0026 Ultra-mutated patients with POLE or POLD1 mutations exhibits distinct pattern between races and primary sites in colorectal cancer (CRC). (18th November 2020) - Cai, Wen; Wu, Dehao; Wang, Li dong; Zheng, Shu; Hu, Hanguang; Ge, Weiting
Abstract : Background: POLE/POLD1 mutation leads to ultra-mutated phenotype in colorectal cancer (CRC) and could be a promising marker for immunotherapy. Methods: We sequenced 338 CRC patients in Asian and obtained 284 white CRC patients from TCGA. Results: The prevalence of POLE/POLD1 mutations were different in racial (6.51% vs 11.27%; P =0.036) (table 1 ). The right-sided colon shows the highest rate of POLE/POLD1 mutations in both group (50% vs 65.63%, P =0.251), while Asian has a higher rate in the left-sided colon than White (36.40% vs 9.38%, P =0.016). We further calculate the prevalence of POLE/POLD1 mutation in different primary sites which proved prevalence are different depending on race (10.35% Asian vs 1.51% White; P =0.027). Conclusions: We firstly report primary sites and racial heterogeneity of POLE/POLD1 mutation in CRC to call for more attention when designing clinical trials and data analysis.